Burnout Syndrome Analysis Among Healthcare Providers Involved in the COVID-19 Pandemic - Mihai MEHEDINTU (Communications of International Proceedings, 2021)
The emergence of the COVID-19 pandemic and its rapid spread all around the world pose a major threat to humanity, and one of the most exposed categories of people is the healthcare professionals. The main purpose of this study is to find out to what degree the burnout syndrome established among healthcare professionals involved in treating COVID-19 patients. The burnout syndrome is an increasingly common phenomenon widespread in several areas, greatly affecting healthcare professionals. Multiple factors such as the busy schedule, performing long night shifts, direct interaction with the suffering and illness of patients on a daily basis and continuous exposure to viruses bring a major contribution to the establishment of the burnout syndrome among healthcare professionals. Another factor that contributes to the onset of the burnout syndrome among physicians is the ever-changing medical environment. A quantitative research method was performed using the survey method. The questionnaire was applied on a convenience sample of 195 healthcare workers involved in treating COVID-19 patients (including physicians, nurses, carers and stretcher-bearers and also administrative personnel) from one of the main COVID-19 hospitals in Bucharest, Romania.
Keywords: Burnout Syndrome; COVID-19; Healthcare; Relationship Marketing